Do Foreigners Pay Higher Rents for the Same Quality of Housing in Geneva and Zurich? - Andrea Baranzini; Caroline Schaerer; José V. Ramirez; Philippe Thalmann (Swiss Journal of Economics and Statistics, 2008)
The Geneva and Zurich housing markets are characterised by high proportions of foreigners and a large share of rental housing. This provides ideal conditions for testing whether foreigners pay more for the same quality of housing than Swiss households and whether flats in neighbourhoods with higher proportions of foreigners rent at a discount. Hedonic price equations using a rich dataset on dwellings and their occupants yield evidence of such discrimination and prejudice. They also suggest more complex relationships between tenant nationality, housing and neighbourhood quality, and rents.
Keywords: R31; R52; D63; 330; housing market; rental market; hedonic model; discrimination; prejudice